Inter-ethnic relations in Padang of West Sumatra; Navigating between assimilation and exclusivity - Elfira, Mina (UI Scholars Hub, 2011)
This article contributes to the discussion on how inter-ethnic relations challenge cultural boundaries, in this case Minangkabau matrilineal-Islamic culture in Padang of West Sumatra, Indonesia. This paper will focus on how Minangkabau people establish relationship with other ethnic groups in Padang, a multi-ethnic city. The paper argues that matrilineal principles (descent and inheritance through the maternal line) and Islam are the defining aspects to be considered by Minangkabau people in maintaining relationship with other ethnic groups. Moreover, there is some interplay between the need to protect Minangkabau Islamic-matrilineal adat in maintaining inter-ethnic relations by Minangkabau people and their assimilation and exclusivity interests.